2006
DOI: 10.1179/174329306x153187
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on resistance spot welding of galvannealed HSLA steel

Abstract: A systematic variation of the parameters involved in the spot welding by electrical resistance of galvannealed strips was carried out on samples from a 2 mm thickness galvannealed high strength low alloy steel strip used for automotive applications. The varied parameters in the present study were welding current, welding time, holding time after welding and number of welding pulses, while the dimensions and characteristics of the electrodes and the applied force during welding were kept constant. The wear of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Generally, the RSW failure occurs in two modes: interfacial and pullout. [6][7][8] Figure 1 shows a typical fracture mode during mechanical testing of a spot weld. In the interfacial mode, failure occurs via crack propagation through FZ, while in the pullout mode, failure occurs via the nugget withdrawal from one sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the RSW failure occurs in two modes: interfacial and pullout. [6][7][8] Figure 1 shows a typical fracture mode during mechanical testing of a spot weld. In the interfacial mode, failure occurs via crack propagation through FZ, while in the pullout mode, failure occurs via the nugget withdrawal from one sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Nietol et a!. [26] investigated various parameters that are used to control the characteristics and properties of galvannealed HSLA steel sheets welded by means of electrical resistance, for further applications at high production speeds. They found that increasing the hold time from 5 to 30 cycles results in stamps free of oxide as shown in Figure 2.8, but care has to be taken, as the amount of ferrite present within the welded nugget is reduced, and the micro hardness of the material increases with increasing the hold time.…”
Section: Recent Studies On Resistance Spot Welding Of Hsla Steelmentioning
confidence: 99%
“…When the electrode force was too high, the weld nugget diameter was small and the tensile shear load was low [4]. For the effect of hold time, Nieto et al [8] concluded that the microhardness of HSLA galvanised steel RSWs increased with the increase of hold time. Pouranvari et al [9] found that hold time had no significant effect on weld nugget diameter, tensile shear strength and fracture mode of low carbon steel RSWs.…”
Section: Introductionmentioning
confidence: 99%
“…The main optimisation methods include adjusting welding parameters (welding current, welding time, electrode force, etc.) [3-9], using a cover plate on the aluminium alloy sheet [10, 11] and using interlayers [12, 13]. For the influence of welding parameters on the quality of RSWs, research results have shown that increasing welding current or welding time leads to thicker IMC layers, larger weld nugget diameter and more molten aluminium alloy expulsion [3-7].…”
Section: Introductionmentioning
confidence: 99%